Investigation on the influence of AC electric filed and KCl on the structure and gel properties of Konjac glucomannan. (30th August 2022) - Wang, Li-Xia; Dao, Li-Ping; Guo, Qi-Yong; Chen, Tian-Long; Fu, Li-Jun; Zhou, Feng-Chao; Yuan, Yi
Highlights: Konjac glucomannan can aggregate under AC electric field and KCl. Electric treatment time and KCl were important for the gel formation. K + and Cl − ions adsorb on hydroxyl group of KGM. KGM partially deacetylate under AC and KCl. KGM electrogel has good thermal stability. Abstract: The influence of alternating current (AC) electric field and KCl on the structure and gel properties of Konjac Glucomannan (KGM) were studied in this work by high-performance gel permeation chromatography (HPGPC), acid-base titration, solid-state nuclear magnetic resonance (NMR), X-ray diffraction (XRD), simultaneous differential scanning calorimetry/thermo gravimetric analyzer (DSC/TGA) and a rheometer. HPGPC showed KGM was degraded by AC electric field and Acid-base titration showed that under the action of AC electric field and KCl KGM removed part of acetyl groups, which were consistent with the analysis of NMR. XRD and temperature sweep measurements respectively showed that the electrotreatment time and KCl concentration had important effects on the gel formation and its three-dimensional network. Simultaneous DSC/TGA and temperature sweep measurements both demonstrated the gel had good thermal stability.